Global warming returns vineyards to Polish lands - Miętkiewska-Brynda, Joanna; Makowski, Jerzy (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Poland is not a country that anyone would associate with wine culture and wine landscapes, although this was not the case in the past. Until the end of the European medieval period, in the south and southwest of the lands of contemporary Poland, vineyards were a frequent feature of the cultural landscape and wine, regardless of self-consumption, was a lucrative object of trade with the Scandinavian countries (without compete with Mediterranean countries). The Little Ice Age and wars, followed by the partition of Poland between powerful neighbors: Russia, Prussia and Austria-Hungary, and a socialist policy of central planning, put an end to wine production in Poland. Today we are witnessing a renaissance of national wine production and the expansion of vineyards on an unprecedented scale. We are also witnessing the return of wine landscapes to Polish lands. The reasons for this return to almost forgotten traditions are complex. In this text we will try to outline them, although it is increasingly clear that global warming is playing an important role in changing the wine map of the world. The change in climate is harming many crops, but the vine in Poland is in favour.